2019
DOI: 10.1097/gme.0000000000001443
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics and properties of estradiol softgel vaginal inserts

Abstract: Objective: TX-004HR is a low-dose estradiol (E2) softgel vaginal insert designed to be rapidly dissolving and mucoadhesive. This report describes the physical attributes and pharmacokinetic parameters of the softgel vaginal insert evaluated for the treatment of moderate to severe dyspareunia due to menopausal vulvar and vaginal atrophy. Methods: In vitro dissolution studies with 25-μg E2 inserts were performed and media samples were analyzed for E2 by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Overall, the results indicated lower systemic exposure with the E2 softgel vaginal insert than with the vaginal tablet comparator (Figure 3; Table 2) [31]. A follow up of this PK study also demonstrated that there were no body position effects (supine vs ambulatory/seated) on the E2 bioavailability with the TX-004 HR inserts [15]. Finally, the PK parameters for TX-004 HR were evaluated in a substudy of the REJOICE trial [32].…”
Section: Pharmacokinetic Datamentioning
confidence: 85%
See 1 more Smart Citation
“…Overall, the results indicated lower systemic exposure with the E2 softgel vaginal insert than with the vaginal tablet comparator (Figure 3; Table 2) [31]. A follow up of this PK study also demonstrated that there were no body position effects (supine vs ambulatory/seated) on the E2 bioavailability with the TX-004 HR inserts [15]. Finally, the PK parameters for TX-004 HR were evaluated in a substudy of the REJOICE trial [32].…”
Section: Pharmacokinetic Datamentioning
confidence: 85%
“…The E2 softgel vaginal insert (TX-004 HR, Imvexxy® [estradiol vaginal inserts]; TherapeuticsMD, Boca Raton, FL) is approved by the FDA at dosages of 4 μg and 10 μg for the treatment of moderate to severe dyspareunia, a symptom of VVA due to menopause [14]. The E2 vaginal inserts are small, light-pink, tear-shaped softgel capsules, which are inserted manually without the use of an applicator in the lower part of the vagina [15]. The outer capsule shell is composed of gelatin polymers to impart mucoadhesive properties and aid in the retention of the capsule in the vagina while allowing fast dissolution and quick release of the medication in the vagina, and complete dissolution by 6 hours after insertion [15].…”
Section: Physical Characteristicsmentioning
confidence: 99%
“…From a patient perspective, such polymers have also assisted in addressing the practical challenges of semi-solid dosage forms, such as leakage [ 37 ]. Mucoadhesive polymers used in soft gelatin capsules of oestradiol provided flexibility of drug positioning, faster dissolution, and higher satisfaction among 85% women, compared to women using conventional vaginal inserts and cream formulations of oestradiol [ 138 ].…”
Section: Vaginal Drug Delivery Systems: History and Present Therapeuticsmentioning
confidence: 99%